The Replacement of Elected Members of The House of Representatives Prior to Inauguration and Principle of Legal Certainty - Valensia Lie; Bachrul Amiq; Zevanya Gerdiman (Universitas Negeri Surabaya, 2025)
General elections are the main means of realizing people's sovereignty in Indonesia's democratic system, which is based on the principle of the rule of law. In practice, legal issues arise regarding the mechanism for replacing elected members of the House of Representatives of the Republic of Indonesia (DPR RI) before their inauguration, especially when the replacement is not entirely based on the highest number of votes. This condition has sparked debate regarding its compatibility with the principles of legal certainty and democracy. This study aims to analyze the compatibility of the mechanism for replacing elected DPR RI members prior to inauguration with the principle of legal certainty and to examine the legal consequences of this practice. The research uses a normative legal method with a legislative, case, and conceptual approach. The legal materials consist of primary legal materials in the form of legislation related to elections and secondary legal materials in the form of literature and legal doctrine. The analysis is conducted in a prescriptive-analytical manner. The results of the study indicate that the provisions on the replacement of elected candidates in Law No. 7 of 2017 on General Elections still contain unclear norms, particularly regarding the reasons for resignation and the authority of political parties in determining replacement candidates. This ambiguity has the potential to cause legal uncertainty, disregard the will of the voters, and reduce the legitimacy of the election results. Therefore, it is necessary to strengthen and affirm election regulations in order to guarantee legal certainty and protect the sovereignty of the people. This article contributes by critically examining the normative ambiguity of pre-inauguration replacement mechanisms and its impact on legal certainty and popular sovereignty.